Soft tissue motion influences skeletal loads during impacts - Challis, J. H.; Pain, M. T. G. (Exercise and Sport Sciences Reviews, 2008)
Soft tissue motion occurs as impulsive loads that are applied to the skeletal system. It has been demonstrated that the wavelike motion of these wobbling masses can reduce the loads acting on the musculoskeletal system. This is an important concept to consider, whether the loads acting on the musculoskeletal system are being determined using either inverse or direct dynamics.